HYBRID WARFARE (VIA LAWFARE) IN ARGENTINA: DETAILS OF AN INVASION (International Seven Journal of Multidisciplinary, 2025)
The purpose of this article is to reflect on one of the expressions of American Hybrid Warfare in Argentina: the use of lawfare to depose governments. In Argentina, there was a major coordinated effort, through the “Case of the Notebooks” (the Buenos Aires version of Operation Car Wash), to prosecute individuals linked to the Justicialist Party (PJ) and sectors of the progressive press, culminating in the conviction of Cristina Kirchner to six years in prison and rendering her ineligible for office. Behind this coordination was an international network composed of judges, mainstream media, and US government agents who, among other actions, carried out extortion, espionage, and secret operations to carry out coups, which became known as “D'Alessiogate.” To achieve this objective, we collected data through bibliographic research.